Electrorheological fluids and magnetorheological suspensions : (World Scientific, 2002)
Proceedings of the Eighth Intl Conference held July 9-13, 2001, in Nice, France. Presents experiments and theories on the rheology of the fluids and its connection with microhydrodynamics and the structure of field-induced aggregates. For researchers and industrialists in the fields of new materials, engineering mechanics, and materials engineering.